The Effect of Training and Motivational Sessions on Sales Performance of Multi-Level Marketing Distributors - Yunandar, Erwin S.A.; Mulyani, Sri; Fa’uzobihi, Fa’uzobihi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the effect of training and motivational sessions on the sales performance of Fohoway distributors. Distributor performance is a key factor in the success of network-based marketing systems (MLM), which rely heavily on individual capabilities in selling products, building relationships, and maintaining performance consistency. This research employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to Fohoway distributors who had participated in the Core Training Camp program and motivational sessions. Data analysis techniques included validity and reliability tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using statistical software. The results indicate that both training and motivational sessions have a positive and significant effect on the sales performance of Fohoway distributors, both partially and simultaneously. These findings provide practical implications for Fohoway management in designing more targeted training and motivational programs to improve distributor performance.